2023
DOI: 10.3390/diagnostics13152545
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of Extracellular to Intracellular Water Is Associated with Permanent Catheter Patency Survival in Patients Receiving Maintenance Hemodialysis

Moo-Jun Kim,
Jae-Wan Jeon,
Hae-Ri Kim
et al.

Abstract: Patients undergoing dialysis through a permanent catheter often experience infection or malfunction. However, few studies have clarified the predictors of permanent catheter patency survival in patients undergoing hemodialysis. We assessed the relationship between the parameters of body composition monitoring (BCM), determined before the initiation of dialysis, and the patency survival of the permanent catheters inserted in 179 patients who commenced hemodialysis between 14 January 2020 and 31 August 2021. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…The results of the BCM parameters were not statistically significant in this study but showed a similar trend to previous studies [ 14 , 15 , 16 ] which showed the association with an ICW decrease and inflammation. Kim et al reported that the parameters ECW/ICW ratio <1.2 and LTI ≥ 10.2 could be useful predictors whether malfunction or infection might affect permanent catheter patency [ 17 ]. The study targeted patients who required dialysis and had a permanent catheter insertion at that time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the BCM parameters were not statistically significant in this study but showed a similar trend to previous studies [ 14 , 15 , 16 ] which showed the association with an ICW decrease and inflammation. Kim et al reported that the parameters ECW/ICW ratio <1.2 and LTI ≥ 10.2 could be useful predictors whether malfunction or infection might affect permanent catheter patency [ 17 ]. The study targeted patients who required dialysis and had a permanent catheter insertion at that time.…”
Section: Discussionmentioning
confidence: 99%
“…The patient population in this study was 75 to 97 years old, with a median age of 82 years. In the study published by Kim et al, the study was not conducted only on elderly people over 75 years of age and did not show statistical significance between permanent catheter patency and nutritional status [ 17 ]. In the case of elderly patients over 75 years of age, nutritional status, especially CONUT score, was shown to be an important factor affecting permanent catheter patency.…”
Section: Discussionmentioning
confidence: 99%